Portable Cartoon Studio : Learn all the secrets of cartooning from the basic to character design to animation - Hart, Christopher (New York : Watson, 1996)
How to draw the cartoon head -- How to draw the cartoon body -- The cartoon animal -- Marrying expression to dialogue -- Advanced techniques
8
Keywords: COMIC